Waste water treatment with Moringa oleifera press cake - Ali, Eman N. (2017)
The consumption of water nowadays is increasing but the production of wastewater from variety of industry and domestic are increasing. If this wastewater is being untreated, it will be wasted and the chemicals inside the water especially heavy metal are harmful to the living organism. There are few conventional method used to treat the wastewater but most of them are costly and hence bio-absorption with the natural coagulant is introduced. One of the multipurpose tree Moringa oleifera, (MO) which is environmental friendly and low cost become a choice for removal of heavy metal from wastewater. The Moringa oleifera press cake (MOPC) are able to remove the heavy metal but the removal efficiency for different metals need to be found out. Therefore, experiment on heavy metal removal by Moringa oleifera press cake was conducted. The wastewater samples and MOPC were collected from Balok River, Kuantan and Mitomasa Sdn Bhd, Kuala Lumpur respectively. MOPC was immersed in distilled water to remove the oil and different concentration of MOPC solution were made. Jar test containing six beakers with 500 mL of sample and different concentration of MOPC solution was operated at 200 rpm for 4 minutes and 40 rpm for 30 minutes. The initial and final heavy metal (Fe, Cu, and Cr) concentration were measured by Atomic Absorption Spectrometer and the removal percentage was calculated. The MOPC removed 69.99% Fe, 88.86 % Cu and 93.73% Cr at optimum concentration of 10000 ppm, 5000 ppm and 15000 ppm respectively. The MOPC also reduced 34.94% of COD and 81.6 % of turbidity. However, BOD of wastewater increase from 9.0 ppm to 18.3 ppm. Besides, pH values did not shown significant changes with the addition of MOPC. The removal of heavy metal was increased proportional with MOPC concentration until optimum removal was reached.